Soloxolone methyl, as a 18βH-glycyrrhetinic acid derivate, may result in endoplasmic reticulum stress to induce apoptosis in breast cancer cells. (15th January 2021) - Alper, Pinar; Salomatina, Oksana V.; Salakhutdinov, Nariman F.; Ulukaya, Engin; Ari, Ferda
Graphical abstract: Highlights: Soloxolone methyl was investigated on breast cancer cells. Soloxolone methyl decreased cancer cell viability and induced apoptosis markers. Soloxolone methyl induced apoptosis triggered by ER stress in MDA-MB-231 cells. Abstract: Being one of the leading causes of cancer death among women, various chemotherapeutic agents isolated from natural compounds are used in breast cancer treatment and consequently studies to develop new drugs still continue. There are several studies on 18βH-glycyrrhetinic acid, a secondary metabolite which is found in Glycyrrhiza glabra (liquorice roots), as a potential anticancer agent. In this study, the cytotoxic and apoptotic effects of Soloxolone methyl compound, a semisynthetic derivative of 18βH-glycyrrhetinic acid were investigated on breast cancer cells (MCF-7, MDA-MBA-231). Soloxolone methyl is found to be cytotoxic on both MCF-7 and MDA-MBA-231 breast cancer cells by inducing apoptosis. Especially in MDA-MB-231 cells apoptosis is detected to be triggered by ER stress. The antigrowth effects of Soloxolone methyl were determined using MTT and ATP assays. To identify the mode of cell death (apoptosis/necrosis), fluorescent staining (Hoechst 33342 and Propidium iodide) and caspase-cleaved cytokeratin 18 (M30-antigen) analyses were used. In addition, apoptosis was investigated on gene and protein levels by PCR and Western Blotting. Soloxolone methyl decreased cell viability on cells in a dose and time-dependent manner and induced apoptosis markers. An increase on apoptotic proteins related to endoplasmic reticulum stress (IRE1-α, Bip, CHOP) was also determined in MDA-MB-231 cells. Moreover, an increase of apoptotic gene expressions was determined in both cells treated with Soloxolone methyl. Advance analyses should be performed to elucidate the potential of Soloxolone methyl as an anticancer agent in breast cancer treatment.